Pengaruh Tipe Persilangan Itik Tegal dan Magelang terhadap Produksi, Tebal Kerabang dan Specific Gravity Telur - Herawati Nur Syafiah; Dattadewi Purwantini; R. Singgih Sugeng Santosa (ANGON: Journal of Animal Science and Technology, 2021)
Background. The objective is to determine the mean and standard deviation egg production, shell thickness and specific gravity cross-type eggs of Tegal and Magelang ducks. The research was conducted in the Poultry Sari duck breeders group, Banjarsari Kulon Village RT 02 / RW 03, Sumbang District, Banyumas Regency. Materials and methods. The material used was 80 ducks from Tegal and Magelang which were divided into 4 types of crosses with 5 replications. Each replication consisted of 1 male and 3 female ducks. The consisted of treatments: P1 (male and female Magelang ducks), P2 (male Magelang ducks and Tegal females), P3 (Tegal males and Magelang females) and P4 (Tegal male and female ducks). The data obtained were analyzed by analysis of variance. Results. Based on the results of the study, it was obtained that the mean and standard deviations of egg production, shell thickness and specific gravity P1 (44.44 ± 15.89; 0.49 ± 0.05 and 1.08 ± 0.02), P2 (35.63 ± 25.52; 0.52 ± 0.06 and 1.08 ± 0.02), P3 (38.22 ± 20.22; 0.54 ± 0.08 and 1.09 ± 0.03) and P4 (22.67 ± 14.72; 0.40 ± 0.03 and 1.09 ± 0.01). The results of the analysis of variance on the type of cross had a very significant effect (P <0.01) on eggshell thickness and has no significant effect (P> 0.05) on egg production and egg specific gravity. Conclusion. Based on the research results, it can be concluded that P1 has better egg production and P3 has better shell thickness and egg specific gravity.